PENGARUH PENGEMBANGAN KARIER DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI UPT DINAS PENDIDIKAN KABUPATEN BANYUASIN - Baidowi Abdhi (Fakultas Ekonomi Universitas Tridinanti Palembang, 2014)
ABSTRACTThis research studies the influence of Career Development and Discipline toward officer Performance at UPT Dinas Pendidikan Kabupaten Banyuasin. This Research was done during 6 ( six) months included design, executing and report the result.The research of this case study aims to know the influence of Career Development and Discipline with officer Performance UPT Dinas Pendidikan Kabupaten Banyuasin either through parsial and also together. The population In this research are the Teacher at UPT Dinas Pendidikan Kabupaten Banyuasin, totally 35 people.Ã‚Â Keywords : Career Development, Discipline of work and PerformanceÃ‚Â